Comparative Analysis of Urban and Rural Public Space Environment Design Based on Multimedia Information. (17th November 2022) - Xu, Huili; Huang, Liyuan
Abstract : At this stage, the most important content of rural construction includes the construction of rural public space, which is related to the environment of all rural areas, the happiness of villagers, and the inheritance and development of rural areas. Especially under the guidance of the rural revitalization strategy, the necessity of public space environment construction has become increasingly prominent, becoming an irreplaceable core content in rural construction. Therefore, we must closely focus on the development needs of rural areas at this stage, dig deep into the development of the public space environment, find corresponding design strategies, and maximize the completion of the real construction of beautiful rural areas. Rural public spaces have experienced the pain of new urbanization and rural intelligence. The most important public spaces in traditional agricultural societies, such as deep-water wells, trees, and sundecks, will slowly decline and fade. In the future, public space in rural areas must function in urban areas. Rural public spaces with complex roles and diverse types of public activities are the main orientations for the transformation of rural spaces in the future.